EEvalauasi Hasil Perencanaan Bangunan Oleh KSO Dua Konsultan Perencana Dengan Pengalaman Kerja Yang Berbeda - kusnul prianto; Muhamad Ratodi (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
The research intends to evaluate the planning design based on the initial mutual check (MC-0) of a large-scale building plan as a result of Joint ventures (KSO) between two planning consultants who differ in planning design experience; one consultant is from Java, and the other is from outside Java. The study's topic is building planning in the Kalimantan region. The design employs descriptive qualitative research based on data from a documentary study of project weekly meeting report archives and data analysis using non-numerical methods such as SWOT analysis. Research results: (1) The weakness of KSO with consultants from outside Java is the difference in experience and work ethic of Human Resources. (2) The obstacle to employing a large number of workers is the difficulty of supervising and coordinating work, which causes errors in the drawing and calculation of the BQ (bill of quantity) volume used in the job auction. (3) The results of the pile indicator analysis conclude that the depth of the precast pile foundation can be reduced. (4) In responding to the preliminary work, the contractor seeks to propose as much additional work as possible and ask for the smallest possible amount of less work. In comparison, the owner seeks to use the remaining funds from less work as additional work costs to increase the function and architectural appearance of the building.